HUBUNGAN FAKTOR PREDISPOCING, ENABLING DAN REINFORCING DENGAN KEIKUTSERTAAN WUS MELAKSANAKAN PEMERIKSAAN IVA - Yunida Turisna Simanjuntak; Julia Siahaan; Masriati Panjaitan (LPPM STIKES Muhammadiyah Kendal, 2021)
Cervical cancer is a malignancy originating from the cervix. In Indonesia, the number of cervical cancer sufferers is the second-highest after breast cancer with a high mortality rate. To reduce the mortality rate, early detection in women of childbearing age (WUS) is carried out using the IVA method. However, the participation rate for IVA examinations is low. This research is a quantitative study with a cross-sectional design that aims to determine the factors associated with the low participation of female prostitutes in conducting IVA examinations. The population of this study was all WUS in the working area of ​​Pustu Sigotom, Pangaribuan District, as many as 869 people. The research sample was taken using a proportional sampling technique as many as 90 people. The analysis of this study used the chi-square statistical test. The data collection technique used a questionnaire. The results of this study indicate that there is a relationship between the variables of knowledge, attitudes, access to information, and husband's support (0,000) and the participation of WUS in conducting IVA examinations and there is no relationship between the variable affordability of the participation distance of WUS to perform IVA examinations (0.692). The implication of this research is expected to increase knowledge about cervical cancer so that attitudes and awareness about the importance of IVA examination are getting better and it is hoped that health workers will be more active in socializing the importance of IVA examination.